MODUL PEMBELAJARAN BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS (STEM) UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN PROSES PESERTA DIDIK PADA MATERI REDOKS DAN SEL ELEKTROLISIS - LHONY LAISNIMA; TIURLINA SIREGAR (Jurnal Ilmu Pendidikan Indonesia, 2020)
This research is a research and development that aims to find out, increase learning outcomes and process skills of students using the Chemistry module by using the module development method. The sample of the research class XII IPA YABT Christian High School. The results showed that: Increased student learning outcomes n-Gain an average of 0.53 with a moderate category. Improved students' process skills by using STEM-based modules on redox material and Electrolysis Cells in the skilled category (78%).